2021 11th International Conference on Information Science and Technology (ICIST) 2021
DOI: 10.1109/icist52614.2021.9440639
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Wiener Filtering for Speech Enhancement In Non-Stationary Noise

Abstract: Speech quality is degraded in the presence of background noise, which reduces the quality of experience (QoE) of the end-user and therefore motivates the usage of speech enhancement algorithms. A large number of approaches have been proposed in this context. However most of them have focused on the case where the noise is stationary, an assumption that seldom holds in practice. For instance, in mobile telephony, noise sources with a marked non-stationary spectral signature include vehicles, machines, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Unsupervised speech enhancement is mostly based on unreasonable assumptions such as smooth noise and uncorrelated speech noise, which leads to weak ability to suppress nonsmooth noise and produces speech distortion. Representative algorithms include spectral subtraction and Wiener filtering [2]. Supervised speech enhancement suppresses noise by learning the statistical properties of the signal, which has obvious advantages in low signal-to-noise environments and nonsmooth noise, and can be divided into two types based on shallow and deep models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsupervised speech enhancement is mostly based on unreasonable assumptions such as smooth noise and uncorrelated speech noise, which leads to weak ability to suppress nonsmooth noise and produces speech distortion. Representative algorithms include spectral subtraction and Wiener filtering [2]. Supervised speech enhancement suppresses noise by learning the statistical properties of the signal, which has obvious advantages in low signal-to-noise environments and nonsmooth noise, and can be divided into two types based on shallow and deep models.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Discrepancies in scope (2) Discrepancies in the description of the research reported (3) Discrepancies between the availability of data and the research described (4) Inappropriate citations (5) Incoherent, meaningless and/or irrelevant content included in the article (6) Manipulated or compromised peer review Te presence of these indicators undermines our confdence in the integrity of the article's content and we cannot, therefore, vouch for its reliability. Please note that this notice is intended solely to alert readers that the content of this article is unreliable.…”
mentioning
confidence: 99%